An Analysis of English Teachers’ Classroom Language in Giving Questions at SMA N 2 Sungai Limau - Meisya Alfino Rosa; Yenni Rozimela (Universitas Negeri Padang, 2023)
The current study aims to find out (1) types of teachers’ questions in an English classroom activity, and (2) types of teachers’ questions in teaching reading and speaking skills in the classroom. The descriptive research method was used in this study with the two teachers in SMAN 2 Sungai Limau as the participants. Observation with guidelines was used to conduct the data, and the data were analyzed by using theory of Farahian-Rezaee (2012). The result of the study showed that three types of teachers’ question in the classroom especially in teaching reading and speaking skills liked display, referential and yes/no questions. However in the process teaching and learning reading and speaking skill teachers’ more used display question than referential and yes/no questions.